Chapter 6 Coordinating international interventions in complex settings An analysis of the EU peace and state-building efforts in post-independence Kosovo - van der Borgh, Chris (Taylor & Francis, 2019)
This paper assesses coordination as a salient capability of international interventions in complex settings characterised by weak states, the dominance of political elites whose interest in reforms is questionable and multiple local and international stakeholders. It focuses on the challenge of integrating a range of national and international actors and multiple policy domains, assessing this operational capability in terms of a Whole-of-Society approach. Using the example of the EU's intervention in Kosovo through the mechanisms of the EULEX mission, and the EU-facilitated Dialogue between Serbia and Kosovo, the paper argues that the EU's impact in Kosovo was weakened by its limited ability to include and engage a broad range of local stakeholders. While a Whole-of-Society approach could address this weakness, the paper also argues that a better understanding of the context-specific opportunities and limitations placed on international organisations like the EU is needed.